The book of Amos and its audiences: prophecy, poetry, and rhetoric - Davis, Andrew R. (Society for Old Testament Study monographs, 2023)
"This book brings the prophetic poetry of the book of Amos into conversation with recent studies of poetry in other disciplines. By distinguishing between the poetic addressee within the text and the actual audience outside the text, the book explores the way poetic discourse is triangulated among multiple audiences"--